Physical–Spectroscopic Study of Charge-Transfer Complexes of Some Purine Derivatives with (π) and (σ) Electron Acceptors - Al–Thib, Anwar; Al–Zaidi, T. (Iraqi Journal of Science, 2024)
Charge-transfer (CT) complexes of adenine (Ade.), guanine (Gua.), xanthine (Xan.), and inosine (Ino.) as electron donors with 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ), 2,3,5,6-tetrabromo-1,4-benzoquinone (Bromanil)(BA) as π – electron acceptors and iodine (Iod.) as σ – electron acceptor were studied and their electronic spectra recorded .In each case one (CT) band was observed and recorded. These spectroscopic investigations made in ethanol solvent at (20°C) temperature. The values of equilibrium constant (KCT), change in standard free energy (ΔG°), molar extinction coefficient (εCT(, absorption band energy (hνCT) of CT complexes and the association energy of the CT complexes-excited state (W) were calculated and studied with discussed. The ionization potential of the donors (IP) were calculated and discussed from the CT complex band lowest energy. The oscillator strength (fCT), transition dipole moment (μCT) and resonance energy (ER) were also calculated and discussed.